Consumer Protection in High Yield Promissory Notes Issued By PT Indosterling Optima Investa - Tobing, Dian Riama L; Sudirman, Lu; Hutahuruk, Rufinus (Journal of Law and Policy Transformation, 2024)
One of the impacts of the COVID-19 pandemic is the default of high-yield promissory notes issued by PT Indosterling Optima Investa. This default case has led to the criminal trial of the CEO of PT Indosterling Optima Investa, who was acquitted, and the PKPU (Postponement of Debt Payment Obligation) decision stipulating the restructuring of interest payments and principal debt to investors. This research aims to determine the form of responsibility of PT Indosterling Optima Investa as the issuer for the losses suffered by investors due to the default of high-yield promissory notes and what legal protections are available for investors against the default of high-yield promissory notes issued by PT Indosterling Optima Investa. The type of research used in this paper is empirical legal research, where law is conceptualized as a social institution that is realistically associated with other social variables.